Penggunaan Kemasan Snack Ramah Lingkungan pada UMKM Kue Moci “Najah” di Kota Semarang - Yani, Tri Endang; Wibisono, Totok; Roestanto, Anantya (Fokus ABDIMAS, 2024)
This community service stems from the discovery of Micro, Small and Medium Enterprises (MSMEs) "Najah" Moci Cakes which still use plastic packaging bags to wrap products purchased by consumers. Plastic packaging is not only dangerous for the sustainability of life for all creatures in the world, but also gives the impression of a less classy product. One way for MSMEs to reduce the negative impact of plastic is by switching to environmentally friendly packaging, namely bags made of paper (paperbags) as product packaging. Apart from being safer for the earth, using paper bags can also give a more elegant impression to a product. The use of attractive paper bags can also function as a promotional tool for a product. This community service aims to educate "Najah" moci cake MSMEs to use attractive and environmentally friendly packaging, thus making it a valuable product. The solution offered is to provide knowledge and assistance in implementing attractive and environmentally friendly product packaging for MSMEs. The method for implementing community service activities is the counseling and mentoring method. This community service has been proven to provide benefits to MSMEs. There has been an increase in partners' knowledge and understanding of the importance of using environmentally friendly packaging. Apart from that, partners have also started implementing environmentally friendly packaging for their products. Keywords: Moci Cake, Packaging, Environmentally Friendly, Promotion, MSMEs